2014
DOI: 10.1007/s12402-014-0140-3
|View full text |Cite
|
Sign up to set email alerts
|

Does distress intolerance moderate the link between ADHD symptoms and number of sexual partners?

Abstract: Previous research demonstrates that ADHD symptoms are related to increased risky sexual behavior. Distress intolerance (DIT) has also been linked to risk behavior and may also be related to increased risky sexual behavior. Thus, we evaluated the degree to which DIT moderated the link between ADHD symptoms and number of casual and monogamous sexual partners. Participants were undergraduate psychology students (N = 660; 30 % male; M = 20.23, SD = 1.40; 47 % European American) who completed an online assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Whereas literature indicates mixed findings for the relations among distress tolerance facets and risky behaviors (De Lisle et al, 2014; Van Eck et al, 2015; Shorey et al, in press), results of the current study are consistent with Simons and Gaher (2005) who found that only absorption and regulation were associated with alcohol use. Our findings suggest that individuals who become overwhelmed and engrossed by negative emotions are more likely to engage in risky behaviors.…”
Section: Discussionsupporting
confidence: 86%
“…Whereas literature indicates mixed findings for the relations among distress tolerance facets and risky behaviors (De Lisle et al, 2014; Van Eck et al, 2015; Shorey et al, in press), results of the current study are consistent with Simons and Gaher (2005) who found that only absorption and regulation were associated with alcohol use. Our findings suggest that individuals who become overwhelmed and engrossed by negative emotions are more likely to engage in risky behaviors.…”
Section: Discussionsupporting
confidence: 86%
“…However, although there has been an abundance of studies on the link between ADHD symptoms and other types of risk taking behaviour, research on the association with RSB has been limited. In the scientific literature, RSB commonly refers to unprotected sex, multiple sex partners, and hazardous sexual activity such as sex while intoxicated [6] and is regarded as a major public health problem during adolescence [7,8]. The handful of previous studies on the association between ADHD symptoms and RSB have been mostly undertaken among adults [9–12] especially males [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…These risky behaviors include increased use of marijuana and illicit substances and increased risk for experiencing both alcohol-related problems and alcohol-use disorders (Rooney et al, 2015) compared to college students without ADHD. Additionally, compared to college students without ADHD, college students with ADHD are more likely to engage in risky sexual behaviors (e.g., unprotected sex) (Van Eck et al, 2015) and non-suicidal self-injurious behaviors (NSSI) (Meza et al, 2016). Given these concerning outcomes, better understanding selfcontrol in college students with ADHD is a clinically important topic.…”
Section: Introductionmentioning
confidence: 99%